A study of superficial surgical site infections in a tertiary care hospital at Bangalore - Golia, Saroj; B, Asha S. Kamath; AR, Nirmala (International Journal of Research in Medical Sciences, 2017)
Background: All postoperative surgical infections occurring in an operative site are termed surgical site infections (SSI). Superficial incisional surgical site infection occurs within 30 days after the operation and infection involves only skin or subcutaneous tissue of the incision and represents a substantial burden of disease for patients and health services. The study was conducted to know the incidence of surgical site infection in our hospital, risk factors associated with it and the antibiotic susceptibility pattern of the pathogens. Methods:This prospective study was carried out in the Department of Microbiology at Dr B R AMC for a period of 1 year from Jan 2013to Jan 2014. Samples of SSI received in the Microbiology laboratory were processed and Data collected. Results:The overall surgical site infection rate in our hospital during the study period is 4.3%. Staphylococcus aureus (S. aureus) was the most common isolate obtained followed by Escherichia coli (E. coli) and Coagulase negative Staphylococcus (CONS). Other organisms isolated were Pseudomonas aeruginosa, Enterococcus, Klebsiella pneumoniae and Proteus mirabilis. Among them, 88.8% of S. aureus and 50% of CONS isolates were methicillin-resistant strains. 80% of E. coli and 100% of Klebsiella species were ESBL producers. 50% of Enterococci were Vancomycin resistant. Risk factors like diabetes mellitus and duration plays a significant role in causing surgical site infection. Conclusion:Implementation of an effective infection control programme and judicious use of antibiotic prophylaxis reduces the incidence of SSI in the hospital.